ANALISIS KANDUNGAN KADMIUM (Cd) PADA UMBI PORANG (Amorphophallus muelleri) PADA BERBAGAI JENIS LAHAN BUDIDAYA DI SULAWESI SELATAN - Fitry Martam; Herman Herman; Zulfitriany D Mustaka; Helda Ibrahim (Percetakan Umi Toaha Makassar, 2026)
Porang (Amorphophallus muelleri) has emerged as an important agricultural commodity in Indonesia, yet food safety concerns related to heavy metal contamination, particularly cadmium (Cd), remain insufficiently explored. This study aimed to analyze Cd concentrations in porang tubers cultivated under different land-use types and to evaluate the influence of land characteristics on Cd accumulation. A quantitative approach with purposive sampling was employed. Nine composite tuber samples were collected from monoculture fields, mixed cropping systems, and home garden environments. Sample preparation involved wet digestion using HNO₃ and H₂O₂ assisted by microwave digestion, followed by measurement using Atomic Absorption Spectrophotometry (AAS). Data were analyzed using descriptive statistics and One-Way ANOVA. The results showed that Cd concentrations ranged from 0.0005 to 0.0262 mg/kg, with the highest average detected in home garden systems (0.0122 mg/kg) and the lowest in monoculture fields (0.0021 mg/kg). However, statistical analysis indicated that land-use type did not significantly affect Cd accumulation (p = 0.298). All measured concentrations remained below the maximum permissible limit established by Indonesian National Standard SNI 7939:2020 (0.05 mg/kg). These findings indicate that porang tubers are currently safe for consumption, although continuous environmental monitoring is necessary to prevent long-term contamination risks.